Educational application of virtual reality in English education in vocational colleges: a bibliometric analysis - Yao, Ling; Sattar Rasul, Mohamad; Omar, Marilssa (International Journal of Evaluation and Research in Education (IJERE), 2025)
Virtual reality (VR) technology has been widely adopted in education field for a period and its application keeps developing continuously. The bibliometric analysis was conducted to provide a comprehensive understanding of VR technology application about research strengths, research theme, scope, hot topics and evolution to enrich further study on VR technology adoption in English education in vocational colleges. The search of literature over the past decade in the Web of Science (WoS) database and 930 articles remained based on inclusion and exclusion criteria. Subsequently, VOSviewer used to analyze data from selected articles. The study finds out that research on VR technology shows an upward trend. The influential country is China, while most research institutions and authors are also from China. Research topics were identified using keyword co-occurrence analysis and four thematic clusters emerged: i) positive impact of VR on English education; ii) VR used in English education for special purpose; iii) VR is used in actual situation with the consideration of its’ features and positive effect; and iv) users’ acceptance of VR. The findings highlight current developments and offer guidance for promoting VR technology utilization in English education. Furthermore, educators could use the findings to design more effective VR-integrated curricula.